Analisis Kejelasan Sasaran Anggaran Sebagai Alat Pengendalian Dalam Meningkatkan Akuntabilitas Di PT.Perkebunan Nusantara III Medan - Shita Tiara; Ova Novi Irama (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2024)
This study aims to determine the clarity of budget targets as a control tool in increasing accountability at PT Perkebunan Nusantara III Medan. The selected budget target is the 2016-2018 palm oil sales budget. The method used in this research is descriptive qualitative research method. The results of the research conducted show that the clarity of the palm oil sales budget target in 2016-2018 can be used as a control tool that can increase company accountability. This can be seen from the process of preparing the budget according to the procedure. As for the budget that is not achieved because it is influenced by several factors, such as exchange rate factors, inflation rates, and rainfall. PT Perkebunan Nusantara III Medan uses PSAK-IFRS accounting principles. The palm oil sales budget report will later be accounted for to shareholders, stakeholders, and interested parties.